THE ROLE OF MATRIX METALLOPROTEINASE MMP-9, ITS INHIBITOR TIMP-1 AND INTERLEUKINE-1β IN PATHOGENESIS OF TRAUMATIC BRAIN INJURY - S. V. Ziablitsev; Ya. S. Yuzkiv; S. V. Kolesnikova; S. V. Pischulina (Kazimierz Wielki University, 2016)
Ziablitsev S. V., Yuzkiv Ya. S., Kolesnikova S. V., Pischulina S. V. The role of matrix metalloproteinase MMP-9, its inhibitor TIMP-1 and interleukine-1β in pathogenesis of traumatic brain injury Journal of Education, Health and Sport. 2016;6(9):955-961. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.193041 http://ojs.ukw.edu.pl/index.php/johs/article/view/4046         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016.   UDC 616.831-001-092:612.017+577.1   THE ROLE OF MATRIX METALLOPROTEINASE MMP-9, ITS INHIBITOR TIMP-1 AND INTERLEUKINE-1β IN PATHOGENESIS OF TRAUMATIC BRAIN INJURY   S. V. Ziablitsev, Ya. S. Yuzkiv, S. V. Kolesnikova, S. V. Pischulina   Bogomolets National Medical University, Kiev, Ukraine   Resume Traumatic brain injury (TBI) is accompanied by high rates of morbidity and mortality in both developed and undeveloped countries that makes it one of the most actual medical and social problems. In recent years matrix metalloproteinases are in increasing interest while studying TBI pathogenesis because of their ability to increase permeability of the blood-brain barrier and to cause nervous tissue matrix reorganization. The goal of given study was to investigate the role of matrix metalloproteinase MMP-9, its inhibitor TIMP-1 and interleukin IL-1β in pathogenesis of TBI. Methods: The study was performed on 98 mature white rats. Moderate severity TBI was modeled with one blow on the cranial vault by means of free-falling plummet. Control group included 30 rats. Cytokines (IL-1b, IL-6, IL-8, TNF-a), MMP-9 and TIMP-1 levels were investigated in animals blood by means of ELISA on 1st, 3rd, 7th, 14th and 21st days after trauma. Results and discussion: MMP-9 levels increased by only 38,2% on the 1st day, but on the 3rd day there was its marked increase to 538%. It is known that metalloproteinases are released from the cells under the influence of various factors, including cytokines. On the 1st day after trauma it was IL-1β which increased by 705% showing the highest rise among other cytokines and exceeding increase in MMP-9 levels. This might indicate regulatory role of IL-1β.  A marked increase in MMP-9 levels in turn lead to TIMP-1 activation. Significant increase in TIMP-1 levels was determined on the 3rd day after trauma. On the 7th day there was a critical period with the highest levels of IL-1β (2147,2%), MMP-9 (720,3%) and TIMR-1 (339,3%). Then all research indicators were decreasing with the most pronounced decrease in IL-1β and MMP-9. Conclusion: MMP-9 levels began to increase on the 1st day after trauma due to influence mainly IL-1β. An abrupt increase in MMP-9 in its turn caused an increase in TIMR-1 levels. Conclusion: Identified changes in IL-1β, ММР-9 та ТІМР-1levels at TBI indicate complex relationships between cytokines and intercellular matrix reorganization regulators in formation of intercellular cooperation and inflammation development. Key words: traumatic brain injury, MMP-9, TIMP-1, IL-1β